The Integral Type Modification of Jain Operators and its Approximation Properties. (10th September 2018) - Mishra, Vishnu Narayan; Patel, Prashantkumar; Mishra, Lakshmi Narayan
Abstract: In the present paper, we discuss the approximation properties of Durrmeyer-Stancu type variant of Jain operators with the modified forms of the Beta basis functions. We establish some direct results, which include the asymptotic formula, the error estimation in terms of the modulus of continuity and weighted approximation. Also, we construct a King modification of these operators which preserves the test functions e 0 and e 1 .